Halal food in New Zealand restaurants: an exploratory study - Wan Hassan, Wan Melissa; Awang, Khairil Wahidin (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
Tourism New Zealand (TNZ) believes that New Zealand, as a major exporter and producer of halal slaughtered meat in the world, can become an attractive destination for Muslim travellers. However, research has also shown that Muslim travellers find it difficult searching for halal food in New Zealand, with many having to prepare their own meals while travelling in the country. This paper is based on a survey that was carried out to investigate the management and promotion of halal food in New Zealand restaurants. Data were collected using a questionnaire that was administered through face-to-face interviews. As the total population of halal restaurants in New Zealand was (and still is) unknown, the snowball sampling technique was used, which resulted with a sample of 99 restaurants. Results show that a huge percentage of the sample did not agree that the Muslim tourist market was significant to their business. Many were also reluctant to promote their halal food or put up the ‘halal’ sign in front of their shop.